The Influence of Foreign Cultural Discourse on the Uma Settlement in Mentawai, Indonesia - Yudas, Yudas; Helmi, Helmi; Elfindri, Elfindri; Asrinaldi, Asrinaldi (ppjbsip, 2023)
The entry of foreign cultures into the Mentawai people made the settlements change. The Mentawai people no longer make Uma a social and economic community. This change was due to the existence of housing and the form of houses built by different Governments. This study aimed to look at outside culture's influence on Uma settlements in Mentawai. This qualitative research method uses ethnographic, sociological, and anthropological approaches using observational data collection techniques, documentation studies, and interviews. Data analysis techniques in this study are data reduction, data presentation, and conclusion or verification. The results of this study show that outside culture has a major influence on the Uma settlement in the Mentawai. Nevertheless, the Siberut archipelago is the only archipelago that has survived despite changes in the housing environment and the shape of houses built by the Government with a description of socio-cultural and economic characteristics, which still survive. This condition still applies today. However, in Sikakap, Sipora, North Pagai, and South Pagai all the uma settlements no longer exist. This is caused by the influence of an outside culture that enters Mentawai society. These external cultural influences are as follows: the entry of foreign cultures into the Mentawai islands, the open nature of the Mentawai people, and the modernization of the form of permanent houses to eliminate uma as the original settlement of the Mentawai people.